Married Women's Wills: Probate, Property, and Piety in Later Medieval England. (11th February 2019) - Beattie, Cordelia
Abstract : This article responds to a debate about the clash between canon law and common law positions on whether married women in England could make wills and what freedoms they had in terms of bequeathing property. In particular, it revises the argument that wives largely ceased to make wills c.1450 by arguing that local customs should be given more attention. The article offers a detailed study of the surviving wills in the deanery of Wisbech 1465–77, its linked diocese of Ely 1449–1505, and the probate acta of the Archdeaconry of Buckingham 1483–97, in order to demonstrate that there was regional variation in the decline in married women's will-making. In particular, a focus on court books, which included visitation material alongside the enrolled wills and probate acta, enables more to be said about the kinds of married women who continued to make wills and their motivations. The article argues that in these areas, as well as a continued tendency for wives who had some land or buildings to make wills, married women who had close connections with men who acted as churchwardens or jurors in church courts were also more likely to have their wills proved, even when they had little to bequeath.